The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/acr.22689
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatologist and Primary Care Management of Cardiovascular Disease Risk in Rheumatoid Arthritis: Patient and Provider Perspectives

Abstract: Objective Despite increased cardiovascular disease (CVD) risk, rheumatoid arthritis (RA) patients often lack CVD preventive care. We examined CVD preventive care processes from RA patient and provider perspectives to develop a process map to identify targets for future interventions to improve CVD preventive care. Methods Thirty-one participants (15 patients, 7 rheumatologists, 9 primary care physicians (PCPs)) participated in interviews, which were coded using NVivo software and analyzed using grounded theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 34 publications
(49 reference statements)
6
72
0
1
Order By: Relevance
“…Far from optimal, these findings might be explained by rheumatologists’ perceived limited role in preventive care. In our prior qualitative interviews, some rheumatologists reported being less likely to identify or manage CVD risk factors (e.g., hypertension, smoking) due to the perception that this is the role of primary care physicians [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Far from optimal, these findings might be explained by rheumatologists’ perceived limited role in preventive care. In our prior qualitative interviews, some rheumatologists reported being less likely to identify or manage CVD risk factors (e.g., hypertension, smoking) due to the perception that this is the role of primary care physicians [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Disagreements were rectified by a third reviewer (CMB) who also oversaw the coding scheme. The coding scheme was informed by prior qualitative work on cardiovascular prevention and clinic‐based care delivery from rheumatology patient and provider interviews and new codes based on current participant data. A detailed summary of the coding scheme is available in , available on the Arthritis Care & Research web site at http://onlinelibrary.wiley.com/doi/10.1002/acr.23858/abstract.…”
Section: Methodsmentioning
confidence: 99%
“…Although many forms of inflammatory arthritis, including ankylosing spondylitis and psoriatic arthritis, are also associated with an increased risk of CVD, associations between smoking, CVD, RA, and SLE have been studied extensively and may be more profound . We therefore focused on RA and SLE, building upon our prior work with these populations .
Patients with rheumatoid arthritis and systemic lupus erythematosus reported that better understanding the negative effects of smoking on rheumatic disease and its treatment would motivate them to quit smoking. Patients who smoke requested point‐of‐care advice in rheumatology clinics on smoking cessation strategies and connections to cessation resources like tobacco quitlines, a free resource in all states. Emphasizing the rheumatology‐specific why and the resource‐specific how of smoking cessation is important when designing and evaluating smoking cessation interventions for use in rheumatology clinics.
…”
Section: Introductionmentioning
confidence: 99%
“…An often debated aspect of CVD risk management has been whether this care should be the domain of the primary care physician (PCP) or the rheumatologist [42, 43]. EULAR recommendations from 2009 and 2017 emphasize that rheumatologists should be responsible for CVD risk management in RA.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have noted gaps in screening for diabetes mellitus [42, 49], and a lack of lifestyle counseling [47, 101]. Reasons for this are likely multifactorial, including lack of time, perhaps lack of knowledge or experience, or a belief that this is managed in primary care [42]. The updated 2017 EULAR recommendations advocate lifestyle counselling, emphasizing the importance of these strategies for overall health.…”
Section: Introductionmentioning
confidence: 99%